Leveraging Technical Library Expertise for Big Data Management. Issue 3 (3rd July 2017) - Johnson, Vanessa
Abstract: Shell Australia's librarians were key stakeholders in a project to improve the databases and processes used to manage the company's geophysical data. Geophysical data are challenging to manage: they are complex 'big' data and defy traditional cataloguing. During the project, the librarians collaborated with geophysicists, geophysical data analysts, IT support specialists and database architects. Their contributions as library and information science (LIS) professionals included providing advice on required metadata fields, developing controlled vocabularies and naming conventions, defining required search parameters, identifying opportunities for added functionalities, undertaking database testing and providing feedback, populating the database and developing procedures. The librarians brought a long-term perspective to the review of geophysical data management, essential for data preservation beyond the business cycle. Cross-disciplinary engagement led to the implementation of tools and processes that provide improved metadata capture, clearer connections between projects and data, improved search functionality and better data management. Collaboration provided the librarians with an opportunity to learn more about geophysical data and its life cycle, and provided an opportunity to demonstrate the value of LIS skills in big data management.